055 Successful application of a novel restitution gradient based marker of ventricular arrhythmia to patients with non-ischaemic conditions. (16th May 2012) - Smith, M I; Nicolson, M B; Brown, P; Tuan, J; Sandilands, A J; Stafford, P J; Schlindwein, F S; McCann, G P; Ng, G A
Abstract : Background: There are major limitations with Sudden Cardiac Death (SCD) risk assessment, especially in patients without ischaemic heart disease (IHD). Electrical restitution, that is, . the relationship between action potential duration (APD) and preceding diastolic intervals (DI), is regarded as key to the initiation of ventricular arrhythmias (VAs). We have developed a novel measure of APD restitution heterogeneity based on 12-lead ECG recordings: Regional Restitution Instability Index (R2I2), and shown it to be predictive of VA/death in patients with established myocardial infarcts.1 This data represents the first application of R2I2 to patients at risk of SCD with non-ischaemic aetiologies. Method: A blinded retrospective study of 57 patients without IHD [Cases], undergoing ventricular tachycardia stimulation studies as SCD risk stratification for ICD, and 29 patients with structurally normal hearts [Controls] undergoing electrophysiology studies for supraventricular arrhythmias. Cases consisted of: 33 patients with dilated cardiomyopathy, 12 Brugada syndrome, 4 non-compaction cardiomyopathy, 3 myotonic dystrophy, 2 arrhythmogenic right ventricular dysplasia, 1 hypertrophic cardiomyopathy and 1 cardiac sarcoidosis. During programmed stimulation, surrogates of APD and DI were obtained from a high resolution surface ECG recording. Restitution curves were plotted with gradients for each lead calculated using overlapping least-squares linear segments.2 APD restitution gradient heterogeneity was measured and quantified as R2I2 (mean of the SD of the residuals from the mean at each segment for each ECG lead). Results: R2I2 was significantly higher in Cases compared to Controls (mean ±SEM: 0.98 ±0.04 vs 0.63 ±0.04, p<0.001) (scatter plot). Six Cases reached the endpoint of VA/death (mean follow-up 5.2 years). There was a non-significant trend towards higher R2I2 in patients experiencing VA/death (1.12±0.10 vs 0.96±0.05, p=0.27). The graph shows the mean cutaneous restitution curve for all leads and all patients, steeper curves with longer QTp (APD) were seen in the Case group. Conclusion: The R2I2 was higher in patients at risk of SCD than controls. Use of cutaneous surrogates to quantify APD restitution heterogeneity and assess risk of SCD shows promise in patients with non-ischaemic aetiologies.